Lino - Curtis; Krabs 1963-; Placid 1961-; Y5/P5 1961- (1985)
First number of the self-issued serial executed entirely in linocuts by members of the French Graphzine movement including KRABS, Placid, Curtis, K Pitou, and Y5/P5
Linoldruck. - Umschlag: in schwarz, gelb und rot, Umschlag mit Gouache zur Geltung gebracht. - Mit Bleistift signiert. - Aufl. 70 Ex.
Keywords: Placid -- 1961-; Krabs -- 1963-; Y5/P5 -- 1961-; Graphzine